(untitled) (Vietnam Journal of Community Medicine, 2024)
Background: Peptic ulcer is a chronic disease with cyclical progression. The lesions are ulcers in the gastric and duodenal mucosa, these ulcers can invade deeper through the submucosa layer; ulcer location in the stomach (gastric ulcer) or in the duodenum (duodenal ulcer). Adherence to treatment helps improve treatment effectiveness and quality of life for patients. Objective: Analyze some factors related to treatment compliance of patients with peptic ulcer disease. Methods: Cross-sectional survey, quantitative research. Results and conclusion: The proportion of women (54.7%) is higher than that of men (45.3%), the age group over 50 years old accounts for 67%. The duration of the disease is over 5 years, accounting for 51.1%. As age increases, the rate of treatment compliance tends to increase: from 18.5% to 28% and 64% (p<0.01). Compared with the group under 30 years old, the likelihood of compliance gradually increases (OR = 1.5 in the 30-50 year old group and up to OR = 76.4 in the over 50 year old group). Male compliance was worse than female (25% vs 73%; OR =9.1, p<0.001). Statistically significant relationship between treatment compliance and patient diet with factors such as overeating, overeating, increasing intake of vegetables and fiber, changing lifestyle and physical activity (p < 0.05).